Pengaruh Whistleblowing System dan Sistem Pengendalian Internal terhadap Pencegahan Fraud dengan Moralitas Individu sebagai Variabel Moderasi - Isbandi, Alya; Fauzihardani, Eka (Universitas Negeri Padang, 2025)
The study aims to examine the impact of the whistleblowing system and internal control system on fraud prevention with morality as a moderating variable. The theoretical foundation used in this research is the gone theory. The sampling method employed is purposive sampling, with respondents being employees of the Padang City Government Office. The respondents include employees holding positions as Head of Division and those in the Finance Department. The type of data used in this study is primary data, using a questionnaire distributed directly to 22 Padang City Government Office. The statical method used in this research is moderation regression analysis using IBM SPSS Statistics version 26. The statistical test result indicates that: (1) The whistleblowing system has a significant positive effect on fraud prevention; (2) The internal control system has no effect on fraud prevention; (3) Individual morality as a moderating variable is not able to moderate the effect of whistleblowing system on fraud prevention; (4) Individual morality is able to moderate the effect of internal control system on fraud prevention.